Anti-inflammatory and antinociceptive activity of pods of Caesalpinia pulcherrima - Manoj Kumbhare, Thangavel Sivakumar (Journal of Applied Pharmaceutical Science)
Present study evaluates the Anti-inflammatory and antinociceptive activities of various extracts of pods of Caesalpinia pulcherrima using various experimental models. The analgesic activity pods of Caesalpinia pulcherrima carried out using acetic acid-induced writhing in mice and tail flick test in rats. The anti-inflammatory activity was evaluated using carrageenan-induced rat paw edema and cotton pellet-granuloma formation in rats. The effects of the administration of reference standard (diclofenac) were also evaluated. Two different extracts (Petroleum ether and Methanolic) of Caesalpinia pulcherrima at the dose level of 100,200 and 400 mg/kg, p.o. were tested. Treatment with Methanol extract (100, 200, and 400 mg/kg, p.o.) showed significant (p
Keywords: Acetic acid, carrageenan, granuloma formation, Caesalpinia pulcherrima, tail flick.